CHALLENGES AND EFFORTS TO IMPROVE THE PERFORMANCE OF VILLAGE APPARATUS IN PUBLIC SERVICES: A QUALITATIVE STUDY IN SALUT VILLAGE - Safitri, Natila Rizka; Ilmam, M.Adib Zatta (UIN Mataram, 2025)
This study aims to evaluate the performance of village apparatus in the implementation of public services in Salut Village, Kayangan District, North Lombok Regency. The approach used is qualitative descriptive with data collection through interviews, observations, and documentation. The results of the study show that the performance of village apparatus in general has gone well, especially in terms of discipline, work spirit, and the ability to complete administrative service tasks. The use of Village Information System (SID) technology makes a significant contribution to service efficiency, although there are still technical obstacles such as power outages and limited infrastructure. Efforts to improve performance are carried out through regular coordination meetings, technical guidance training (BIMTEK), and periodic evaluations. The obstacles faced include limited human resources, double workload, and disagreement with community expectations. This study concludes the need to increase the capacity of apparatus and improve technological infrastructure to support optimal public services at the village level